Perjanjian Indonesia Malaysia - Edi Budi Mulia; Tamaulina Br. Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
Diplomatic relations between Indonesia and Malaysia have long been established since the independence of the two countries. Over the years, various agreements have been agreed to regulate various aspects of bilateral cooperation, ranging from economics, security, borders, to culture. One important agreement is the Maritime Boundaries Agreement agreed in 1969, which established maritime boundaries between the two countries in the Strait of Malacca and the South China Sea. Apart from that, there is also an agreement regarding the protection of Indonesian workers in Malaysia, which aims to protect the rights of migrant workers. These agreements reflect the commitment of both countries to maintain harmonious and mutually beneficial relations. However, challenges remain, such as occasional border disputes and issues regarding the treatment of migrant workers. Through dialogue and diplomacy, Indonesia and Malaysia continue to strive to resolve these problems and strengthen cooperation in various fields.